Estimation of Homocysteine and its Relationship with Vitamin B12 and Folic Acid Levels in Patients with Cardiovascular Disease - Zaalan, Ahmed; Jasim, Hind; Farhan, Huda (University of Thi-Qar Journal of Science, 2025)
Globally, one of the leading causes of death is cardiovascular disease (CVD). The plasma levels of homocysteine rise after myocardial ischemia and are involved in numerous methylation processes. This study aimed to evaluate homocysteine levels and their relationship with vitamin B12 and folic acid (vitamin B9) in patients with cardiovascular disease and early-stage heart disease due to hypertension, lipidemia, etc. The present study included 120 participants aged between 30 to 70 years and was divided into three groups. Forty patients with acute myocardial infarction (G1), forty patients with early-stage heart disease (G2), and forty healthy participants (G3). Quantitative determination of homocysteine, vitamin B12, and vitamin B9 is measured based on the competitive enzyme-linked immunosorbent assay (ELISA) technology. Acute myocardial infarction and early-stage heart disease patients also had their total cholesterol, triglyceride, HDL, and LDL levels examined. The study showed that raised homocysteine levels are linked with deficiencies in vitamin B9 and vitamin B12 (P ≤0.0001). A highly significant positive correlation between homocysteine and lipid profile between G1 and G3, and G2 and G3 (P-value≤0.0001). Also, a significant positive correlation exists between homocysteine and triglyceride between G2 and G3 (P-value=0.012). A negative correlation between homocysteine, vitamin B9, and vitamin B12 at G1, G2, and G3 groups (P-value≤0.0001). The study’s findings indicated that increased homocysteine levels, which are caused by deficiencies in vitamin B12 and vitamin B9, raise the risk of cardiovascular disease.